The Association Between Full-Day School and High School Students’ Concentration and Understanding of Mathematics - Rendi Fitrah Handoko; Lily Rohanita Hasibuan; Laili Habibah Pasaribu (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Full-day school not only serves as a system for fostering excellent concentration and understanding in children's learning, but also hones their ability to think relevantly and adds enthusiasm to their pursuit of knowledge. This study aims to determine the significant impact of full-day school on students' concentration and understanding of mathematics. The research method used was qualitative, utilizing data analysis such as validation tests, linearity tests, homogeneity tests, and T-tests. The results showed that full-day school had a significant impact, particularly on students' concentration. Initially, students were stable in their learning, but over time, their concentration weakened due to fatigue from prolonged study. This can also impact students' understanding of mathematics. In this study, the effect of full-day school on concentration and understanding of mathematics was 0.464> 0.05 and the calculated t value was 4.303> t table. It can be concluded that Ha is accepted which means there is an effect of full-day school (x) on concentration and understanding of mathematics (y). So from the explanation, it can be seen that the calculated t is greater than the t table, meaning Ho is rejected. There is a significant influence between full day school on concentration and understanding of mathematics in SMA Swasta HAS SEPAKAT.